Physical activity and health guidelines recommendations for various ages, fitness levels, and conditions from 57 authoritative sources - Rahl, Riva L. 1973- (Champaign, IL Human Kinetics, 2010)
Lifting through the numerous guidelines on physical activity and health published by government agencies, professional organizations, and associations can be a daunting task. Information exists in all types of formats and locations--including government documents, press releases, and Web sites--so simply finding those guidelines can be an ordeal. Physical Activity and Health Guidelines puts the current information in one place--at your fingertips. Physical Activity and Health Guidelines compiles the latest recommendations from various leading sources and organizations into a single text. This one-of-kind resource provides quick reference to physical activity and health recommendations for healthy people and for those with chronic conditions across all age groups. All readers--physicians, physical therapists, fitness professionals, and general fitness enthusiasts--will be able to locate individualized recommendations regarding appropriate levels and types of physical activity. Specific activity recommendations for people with diabetes, asthma, osteoarthritis, and cerebral palsy are detailed in this text. Other guidelines for the prevention of common chronic diseases such as cancer, coronary artery disease, osteoporosis, and metabolic syndrome are also shared. This text also includes the following information: The components of exercise program design, which will assist readers in preparing to implement individual and group exercise programs; How physical activity recommendations can help people meet weight-management guidelines; Information on purchasing and using exercise equipment such as treadmills, heart rate monitors, weight training machines, and exercise videos; Guidelines for cardiac testing and other exercise testing to assist in the implementation and evaluation of physical activity programs as well as the assessment of the safety of these programs for people with chronic conditions. For ease of use, Physical Activity and Health Guidelines presents information in a consistent format for each entry, including the date issued or most recently updated, the issuing organization, appropriate population, and location of the guidelines (with Web sites when available). Recommendations are given for aerobic, resistance, and flexibility training; further specifications regarding the frequency, intensity, duration, and type of activity are included. An appendix lists additional resources divided by topic and includes Web addresses of key organizations, statements, and other physical activity and health-related tools. Physical Activity and Health Guidelines is the first text to gather the wealth of information regarding physical activity, exercise, and health needs and recommendations into a single source. Convenient and easy to use, this unique text will help readers understand the requirements for safe and effective physical activity for all people regardless of health conditions, and it offers the basic knowledge and tools for designing and implementing appropriate physical activity programs.
Part I. General Health and Fitness Guidelines -- Chapter 1. Exploring the Relationship Between Physical Activity and Health ; History and Development of Physical Activity Guidelines ; Basic Concepts and Definitions ; Changes and Benefits Resulting From Physical Activity ; Risks of Physical Activity ; Patterns in Physical Activity Participation ; Summary -- Chapter 2. Exercise Guidelines for Physical Fitness and Health ; Most Recent National Guidelines in the United States ; Significant Historical Guidelines ; Specialized Guidelines ; State and International Guidelines ; Summary -- Chapter 3. Guidelines for Personal Exercise Programs ; Basic Definitions and the FITT Principle ; Components of Physical Fitness ; Guidelines for Individualized Exercise Prescription ; Summary -- Part II. Physical Activity Guidelines by Population -- Chapter 4. Infants and Toddlers ; Guidelines From the American Academy of Pediatrics ; Guidelines From Other Organizations ; Guidelines for Prevention of Obesity and Chronic Disease ; Physical Activity as Play and Nutritional Goals for Children ; Summary -- Chapter 5. School-Aged Children ; Basic Facts About Physical Activity and Health in Children ; Establishment of the Earliest Guidelines for Children ; Landmark Guidelines ; School and Community Health Guidelines ; Guidelines Outside of the School Environment ; International and State Guidelines ; Guidelines Focused on Specific Health Goals ; Summary -- Chapter 6. Pregnant and Postpartum Women ; Encouraging Pregnant Women to Be Physically Active ; Benefits and Risks of Physical Activity for Pregnant Women ; Primary Concerns of Exercise and Physical Activity During Pregnancy ; Guidelines for General Exercise Prescription ; Important National and International Guidelines ; Benefits and Risks of Physical Activity During the Postpartum Period ; Summary -- Chapter 7. Older Adults ; Benefits of Physical Activity for Older Adults ; Major National Guidelines ; Other National Guidelines ; International and State Guidelines ; Guidelines for Adults Who Are Frail or at Risk for Falling ; Contraindications to Exercise ; Summary -- Part III. Physical Activity Guidelines by Disease States -- Chapter 8. Cancer Prevention and Optimal Cardiometabolic Health ; How Exercise Reduces the Risks of Cancer ; General Cancer Prevention Guidelines ; Guidelines for Specific Types of Cancer ; Metabolic Syndrome ; Type 2 Diabetes ; Summary -- Chapter 9. Cancer ; Benefits of Physical Activity ; American Cancer Society Guidelines ; Other Notable Guidelines ; Guidelines for Specific Cancers ; Side Effects of Cancer Affecting Physical Activity ; Summary -- Chapter 10. Hypertension and Cardiovascular Disease ; Benefits of Exercise for Hypertension ; American College of Sports Medicine Guidelines ; International Guidelines ; Guidelines for Coronary Artery Disease ; Summary -- Chapter 11. Arthritis and Osteoporosis ; Rheumatoid Arthritis ; Osteoarthritis ; General Arthritis Guidelines ; Osteoarthritis Guidelines ; Osteoporosis ; Guidelines for Prevention of Osteoporosis ; Guidelines for Individuals With Osteoporosis ; Summary -- Chapter 12. Diabetes ; Benefits of Physical Activity for Preventing and Managing Diabetes ; Potential Concerns Regarding Physical Activity ; Guidelines for Individuals With Type 2 Diabetes ; Guidelines for Individuals With Type 1 Diabetes ; Summary -- Chapter 13. Neuromuscular Disorders ; Benefits of Physical Activity ; General Recommendations From Physical Activity Guidelines for Americans ; Guidelines for Cerebral Palsy ; Guidelines for Parkinson's Disease ; Guidelines for Muscular Dystrophy ; Guidelines for Multiple Sclerosis ; Guidelines for Spinal Cord Injury and Disability ; Guidelines for Stroke and Brain Injury ; Summary -- Chapter 14. Asthma ; Exercise-Induced Asthma ; General Guidelines for People With Asthma ; Guidelines for Children With Asthma ; Summary -- Part IV. Guidelines for Exercise Testing and Prescription and Beyond -- Chapter 15. Exercise Testing and Prescription ; Standards for Exercise Testing in Adults ; Benefits of Exercise Testing for Children ; Summary -- Chapter 16. Cardiac Exercise Testing and Prescription ; Candidates for Testing Utility of Information Acquired From Exercise Testing ; Protocols for Exercise Testing ; Exercise Testing Procedures ; Other Methods of Cardiac Testing ; Summary -- Chapter 17. Dietary and Weight Management Guidelines ; Basic Facts About Body Weight ; Dietary Guidelines From National Organizations ; International Dietary Guidelines ; Hydration, Energy, and Supplementation During Activity ; Dietary Guidelines for Special Populations ; Dietary Guidelines for Various Diseases ; Summary -- Chapter 18. Exercise Equipment and Facilities ; Aerobic Exercise Machines ; Weights ; Tools for Monitoring Physical Activity ; Exercising at Home ; Exercising in a Workout Facility.
Includes bibliographical references
Keywords: Exercise; Health; Physical fitness